2006
DOI: 10.1111/j.1742-4658.2006.05174.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient silencing of Plasmodium falciparum bifunctional glucose‐6‐phosphate dehydrogenase− 6‐phosphogluconolactonase

Abstract: Malaria is a major health hazard in tropical and subtropical areas around the world. In Africa alone, every year over a million children under the age of 5 years die of malaria and around 300-500 million people are infected by the parasite [1,2]. Added to this, the appearance of parasites resistant to antimalarial drugs is on the increase and it is not proving easy to develop an efficient vaccine against Plasmodium falciparum. There is thus a need for new therapeutic targets.The sequencing of the P. falciparum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…These data suggest that PfPKA activity might be necessary for the completion of the asexual cycle, or the reinvasion of erythrocytes. For further dsRNA experiments, we decided to analyze the treated parasites at the maximum of PfPKAc expression which occurs at the schizont stage according to previous studies (Wu et al 1995;Crooke et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest that PfPKA activity might be necessary for the completion of the asexual cycle, or the reinvasion of erythrocytes. For further dsRNA experiments, we decided to analyze the treated parasites at the maximum of PfPKAc expression which occurs at the schizont stage according to previous studies (Wu et al 1995;Crooke et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Growth of P. falciparum with RNAimediated silencing of PfGluPho arrests at the trophozoite stage and results in increased gametocyte formation, highlighting the importance of PfGluPho for Plasmodium parasites. Furthermore, it was shown that PfGluPho silencing was accompanied by enhanced transcription of thioredoxin reductase, pointing to a key role of PfGluPho in responding to oxidative stress (68). However, studies on RNAi in Plasmodium parasites raise questions about the significance of RNAi-based study results, because the RNAi machinery is missing in Plasmodium (69).…”
Section: P Falciparum's G6pdmentioning
confidence: 99%
“…This indicates either that PfGluPho is essential in blood stage parasites or that loss of this enzyme is highly deleterious. A previous analysis of PfGluPho attempted to ablate GluPho function by knocking down the PfGluPho transcript via antisense silencing or by overexpression of PfGluPho dsRNA [20]. These methods are not routinely used in P. falciparum genetic manipulation, and the method by which they are proposed to work is unclear.…”
Section: Pfglupho Is Essential For Blood Parasite Stage Growthmentioning
confidence: 99%